Stroke variables of junior paddlers in 200-m sprint kayaking - Hirano, T.; Kashiwagi, Y.; Kobayashi, T.; Fujito, Y.; Yamagishi, M.; Kato, T.; Funato, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Sprint kayak is competed over 200-m, 500-m, and 1000-m distance. In theoretically, kayak velocity (Vkayak) is a product of stroke rate (SR) and displacement per stroke (DPS). However, previous study has not been reported these classical variables of junior paddlers. Therefore, the purpose of this study was to clarify the relationship between the Vkayak and stroke variables in the junior paddlers of the 200-m sprint kayaking. Methods: We analyzed 52 junior male paddlers (Race time: 43.177±2.044sec). Also, subjects were divided into Good (n = 12, Race time: 40.486±1.154sec) and Poor (n = 15, Race time:45.583±1.116sec) groups according to race time. The race movies were collected at the Japan Canoe Sprint Junior Championship in 2015 in Fujikawaguchiko-machi using three video cameras. During the competition, three parts of durations; 0-25m (Initial part), 100-125m (Middle part), and 175m-200m (Finish part) were selected for the analysis such as Vkayak. In each part, consecutive 6 stroke time was determined for the calculation of the SR. DPS was calculated by dividing the Vkayak at the SR. Pearson`s correlation coefficients were used to examine the relationships between Vkayak, SR, and DPS in all subjects. Further, the two-way repeated ANOVA was performed to examine the effect of different groups and sections on Vkayak, SR, and DPS. A Bonferroni post hoc multiple comparison test was performed if a significant main effect was observed. In each statistical analysis, the level of significance was set to be p < 0.05. Results and Discussion: A significant positive correlations were found between Vkayak and SR (Initial part: r = 0.401, p < 0.01, Middle part: r = 0.733, p < 0.001, Finish part: r = 0.535, p < 0.001). In addition, a significant positive correlation was found between Vkayak and DPS only at the Initial part (r = 0.382, p < 0.001). These results of the presents study agrees with past findings that SR was significantly related to kayak velocity in adult paddler due to the decrease water phase time [McDonnell et al. 2013]. Vkayak and SR of initial, middle, and finish was significantly higher in the good groups (p < 0.01, p < 0.01), however, DPS was did not differ between two groups. According to a previous study, SR of international adult paddlers was higher than in the national paddlers (Brown et al. 2011). Thus, these results suggest that the kayak performance time differences between good and poor paddlers can be maintain attributes to SR difference. Conclusions Key factor to improve the performance in the 200-m sprint kayaking should increase the stroke rate without loss of the displacement per stroke.